SERVQUAL method in studying service quality of travel insurance - Przybytniowski, Jarosław Wenancjusz (Business: Theory and Practice, 2023)
Background: The study which consists of two parts: theoretical and empirical ones, and contains the analysis of the concept of insurance service quality in relation to travel insurance by employees of insurance institutions as well as by individual customers. Methods: The research was conducted by means of the SERVQUAL method among individual customers who hold travel insurance contracts in Świętokrzyskie, Małopolskie Lubelskie and Podkarpackie voivodships. The aim of the study was to identify the factors of travel insurance service quality in the conditions of the changing tourist market in Poland, as well as to define the hierarchy of their importance. Result: Moreover, on the basis of the SERVQUAL method, some discrepancies were established between customer expectations and the perceived services. This study is a continuation of the research conducted and another study of the series of studies of service quality in the market of property insurance in the voivodeships of eastern Poland.